2017
DOI: 10.1016/j.nedt.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Including the online feedback site, Patient Opinion, in the nursing curriculum: Exploratory study

Abstract: Experience from these case studies suggests that webinars followed by use of Patient Opinion preparing for placements may be a sustainable way of embedding feedback sites in the nursing curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Six studies 31,36,38,43,45,47 employed digital tools to involve patient, public and users in nursing education. They focused on different types of involvement facilitated by a range of digital tools such as storytelling via video or digital patient stories, 31,36 online feedback sites, 38,47 videoconferencing 43 and an online discussion forum. 45 The study by Simpson et al showed how the students worked with online discussion forums using an innovation method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies 31,36,38,43,45,47 employed digital tools to involve patient, public and users in nursing education. They focused on different types of involvement facilitated by a range of digital tools such as storytelling via video or digital patient stories, 31,36 online feedback sites, 38,47 videoconferencing 43 and an online discussion forum. 45 The study by Simpson et al showed how the students worked with online discussion forums using an innovation method.…”
Section: Resultsmentioning
confidence: 99%
“…In this manner, the method made non-clinical engagement with patients and service users more feasible. 38 The study by Christiansen indicated that a narrative method using digital patient stories may be a beneficial way to learn. This method created an opportunity for nursing students to transcend their frame of reference and engage with the reality of others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, for students, the nursing curriculum should be considered in terms of empathy, patient-centeredness, cultural awareness, and probably greater understanding of public health and the social determinants of health. 2 But, improving effective curriculum has been a challenge. The preparation of nursing curriculum is inadequate to face inequalities and present curriculum challenges because the curriculum is obsolete, defective, and constant.…”
Section: Introductionmentioning
confidence: 99%